2010
DOI: 10.1111/j.1365-2044.2010.06249.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between nitrous oxide and the incidence of postoperative nausea and vomiting in adults: a systematic review and meta‐analysis

Abstract: SummarySome, but not all studies have suggested intra-operative use of nitrous oxide is correlated with postoperative nausea and vomiting. We performed a meta-analysis of randomised controlled trials to compare the incidence of nausea and vomiting in adults following general anaesthesia with or without nitrous oxide. We retrieved 30 studies (incorporating 33 separate trials) that investigated a 'nitrous oxide group' (total 2297 patients) vs a 'no-nitrous oxide group' (2301 patients). Omitting nitrous oxide sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 75 publications
6
46
0
2
Order By: Relevance
“…6,22 Furthermore, nitrous oxide may increase the incidence of PONV. In a recent meta-analysis by Fernández-Guisasola et al 23 PONV following anaesthesia increased from 27% without nitrous oxide to 33% with nitrous oxide. In previous studies, the incidence of PONV was reported to be as high as 71% when isoflurane and nitrous oxide were used for women who underwent YJ Won, JY Yoo, YJ Chae et al Anaesthetic technique and PONV thyroidectomy.…”
Section: Discussionmentioning
confidence: 96%
“…6,22 Furthermore, nitrous oxide may increase the incidence of PONV. In a recent meta-analysis by Fernández-Guisasola et al 23 PONV following anaesthesia increased from 27% without nitrous oxide to 33% with nitrous oxide. In previous studies, the incidence of PONV was reported to be as high as 71% when isoflurane and nitrous oxide were used for women who underwent YJ Won, JY Yoo, YJ Chae et al Anaesthetic technique and PONV thyroidectomy.…”
Section: Discussionmentioning
confidence: 96%
“…Nitrous oxide should be avoided because the risk of pneumothoraces during the procedure (48) and also because of its effect on post-operative nausea and vomiting (49) which could be particularly harmful due to the presence of the prosthesis and reconstruction. The anaesthesia could be supplemented with a continuous intraoperative epidural infusion or an intravenous target controlled remifentanil infusion (0.1-0.5 mcg/kg/min).…”
Section: Induction and Maintenance Of Anaesthesiamentioning
confidence: 99%
“…This allows for rapid emergence from anesthesia [23] and avoidance of opioidinduced respiratory complications. Although many avoid N 2 O due to concerns of increased incidence of postoperative nausea and vomiting (PONV) and pressure effects through expansion of closed spaces, the clinical significance of these side effects in modern anesthetic practice has been questioned [24]. Importantly, even a minor degree of residual neuromuscular blockade (usually not appreciated clinically) can increase postoperative morbidity including inadequate ventilation, hypoxia, and the need for reintubation [25,26].…”
Section: Intraoperative Considerationsmentioning
confidence: 99%